Gas independence of Miscanthus × giganteus torrefied in nitrogen (N2) and carbon dioxide (CO2) using calibrated thermogravimetric analysis. (September 2019) - Howell, A.; Stahlfeld, K.; Mohammed, A. Balogun; Vijlee, S.; Belmont, E.
Abstract: Effects of torrefaction in N2 versus CO2 environments are not well understood despite their industrial significance. Previous torrefaction studies observed increased mass loss and enhanced biomass properties in CO2, but the underlying mechanisms for these differences have not been thoroughly explored. This study critically examined the commonly used thermogravimetric analysis (TGA) technique to highlight the effects of calibration and environment gas properties on torrefaction in N2 and CO2 at extended residence times using Miscanthus x giganteus . The impacts of environment conditions on mass loss, heating value, grindability and combustion were investigated using TGA and a batch reactor. Results show that rates and extents of changes in these properties are independent of gas environment but dependent on time when respective TGA calibrations are used for N2 and CO2 . This study provides new insights into conclusions drawn by previous studies investigating gas environment impacts, and elucidation of calibration impacts on TGA data. Highlights: Miscanthus torrefied in N2 and CO2 at 250, 275, 300 °C and various residence times. Impacts of TGA calibration on mass loss rates and extents were investigated. Independence of gas environment was found under equivalent biomass heating rates. Mass loss, grindability, HHV and combustion quantified at varying treatment times. Energy yield and enhancement factor were successfully predicted by a simple model.